Жилище: энциклопедия / [ред. А. П. Горкин] - Горкин А. П. (Большая Российская Энциклопедия, 1998)
Экземпляры: ф.6 (2003) / Инвентарный номер: 46005 / Цена: / Сис.шифр: 37. 279 / Авт.знак: Ж 72 / ГРНТИ: 75.35 / ББК: 37. 279я2